The prospective roles of exosomes in pituitary tumors - Lisiewicz, Paulina; Szelachowska, Małgorzata; Krętowski, Adam Jacek; Siewko, Katarzyna (Frontiers in Endocrinology, 2024)
Pituitary neuroendocrine tumors are common, typically benign intracranial neoplasms arising from well-differentiated anterior pituitary cells with prevalence of clinically relevant pituitary tumor of 89 in 100 000 people. Despite the growing number of published studies, there is still a need for diagnostic and predictive biomarkers of pituitary adenomas. Prompt determination of tendency of the tumor for invasive growth and aggressive behavior would allow for earlier and more effective treatment. Extracellular vesicles (EVs), including exosomes, are particles released by cells containing cell-specific cargo including a variety of bioactive molecules, such as DNA, messenger RNA, microRNA, long non-coding RNA, circular RNA, proteins, and lipids surrounded by lipid membranes, which act as mediators of cell to cell communication. The ability of exosomes to reflect the functional state of the tumor, transport informative molecules, and accessibility in body fluids make them promising candidates in the search for biomarkers and new therapeutic methods. This study aims to investigate the involvement of exosomes in the pathology of pituitary adenoma and their potential clinical applications.